Nursing Higher Education System in Austria - Palasiuk, Halyna (Pedagogical Discourse, 2014)
The article deals with the issue of nurse professional training in Austria. The peculiarities of Austrian system of higher education on the basis of degree education are discussed. Particular attention is paid to the matter of preparation of Bachelors, Masters and Doctors of Nursing at the universities and higher educational schools of Austria. The questions of necessity of reforms in the national system of nurse education and studying peculiarities of the nurse professional training in the educational establishments in Austria are argued whereas its system of training of medical workers is considered to be one of the most effective in Europe.